Results of Fullerton Test in older people. Group comparison due to the Nordic Walking and long walks undertaking - Zielińska, Natalia; Ziółkowska, Anna; Winiarska, Angelika; Świtaj, Konrad; Wojtczak, Paweł; Kujawska, Agnieszka; Perkowski, Radosław; Androsiuk-Perkowska, Joanna; Gajos, Małgorzata; Topka, Weronika; et al. (Journal of Education, Health and Sport, 2017)
Introduction: Standardly, high level of physical activity is prescribed to the older patients. However, it is worth to examine if every kind of physical activity give the same amount of health benefits, or is it dependent on its modality. Aim: The purpose of above studies is to measure the differences in Fullerton subtests results in group who does vs in group who does not undertake regular long walks (LW) and Nordic Walking (NW). Material and methods: Subtests of Fullerton tests were used to examine the physical performance of patients. Physical activity questionnaire was used to distinguish groups of patients who do vs do not engage in long walks and Nordic Walking regularly. Results: There were no statistically significant differences in Fullerton scores due to NW-engagement. In contrary, group engaged in LW walked 42.41 meters more in 6-minute walk tests than group who do not undertake such activity. Moreover, Upper Right and Left Limbs Strength tests and its mean scores were better in LW-group by 4.23, 4.6 and 4.09 repetitions, respectively. Conclusions: There was no statistically significant differences in results of Fullerton subtests between group of NW-engaged older people comparing to group who do not undertake NW. Group of participants engaged in long walks had better scores aerobic capacity and upper limbs strength tests.